Touch, Look, Compare, Compress (TLCC) Based On Family Centered Care (FCC) Reducing Phlebitis In Children With Intravenous Therapy - Ely Mawaddah; Mira Utami Ningsih; Dewi Purnamawati; Lale Wisnu Andrayani (Jurnal Keperawatan Terpadu (Integrated Nursing Journal), 2022)
The incidence of phlebitis is an indicator of hospital performance and requires the percentage of phlebitis to be less than 5%. Intensive monitoring of patients who receiving intravenous therapy can reduce complications from phlebitis and improve service to patients. This study aims to determine the effect of the intervention package Touch, Look, Compare, Compress (TLCC) on the incidence of phlebitis in pediatric patients who are infused. This research is an experimental study with a quasi-experimental design, respondents will be divided into 2 groups: The group given the TLCC flyer intervention and the control group given the intervention according to hospital procedures. The measurement of phlebitis uses a phlebitis degree table instrument developed by the Infusion Nurses Society (INS). Measurements were taken on day 1, day 2 and day 3. The results showed an increase in the mean of patients who had phlebitis on day 3 in the control group. There were significant differences in the degree of phlebitis on days 1, 2 and 3 (p value = 0,000) in the control group. In the intervention group there was no significant difference in the degree of phlebitis on days 1, 2 and 3 (p value = 0.368). Statistical test results using Mann Whitney showed no significant difference in the degree of phlebitis in the two groups on day 1 (p = 1.00), while on days 2 and 3 there was a significant difference (p = 0,000). Monitoring pediatric patients with intravenous therapy through TLCC interventions can prevent phlebitis.